Molecular dynamics study of the reinforcement effect of graphene in multilayered polymer nanocomposites. (15th June 2017) - Alian, A.R.; Dewapriya, M.A.N.; Meguid, S.A.
Abstract: We conducted comprehensive molecular dynamics simulations of the nanoindentation of graphene reinforced composites to study the effect of graphene as a reinforcement and coating material. Three different cases are considered: (i) single and multilayered graphene layers used to coat a polyethylene (PE) substrate, (ii) graphene layers embedded into a PE block forming a multilayered system, and (iii) graphene layers randomly embedded into a PE block forming a nanocomposite. The study focused on the reinforcement mechanism and the fracture behaviour associated with increasing the number of graphene coating layers, changing interlayer spacing distance, orienting graphene-PE layers with respect to the indentation direction, and changing graphene dispersion in the composite. The results of our study reveal that the indentation resistance of a single-layer graphene coated PE is fourteen-fold the indentation resistance of pure PE. They also indicate that the indentation resistance of the multi-layered embedded graphene arrangement can be effectively controlled by appropriately selecting the separation distance between the graphene layers. They further show the strong influence of the orientation and the arrangement of graphene layers on the mechanical response of the nanocomposite. These findings are useful in designing graphene-based nanocomposites with tenable performance. Graphical abstract: Highlights: MD simulations are conducted of the reinforcement effect of graphene-coated Polyethylene (PE) substrate to nanoindentation. The work considers the reinforcement response of multilayered graphene layers embedded in a PE block to nanoindentation. The resistance to indentation is improved considerably by the use of single and multilayered graphene sheets. The orientation and dispersion of graphene sheets in the nanocomposite significantly influence the mechanical properties. This work is useful in designing graphene-based nanocomposites and hybrid materials with unique mechanical properties